The Effect of the Problem-Based Learning Model on The Numeracy Ability of Grade X Students in Solving AKM Problems on Opportunity Material - Ilmayasinta, Nur; Febriyanti, Rahma; Kurniyawati, Wifadah (Universitas Tidar, 2024)
This research was conducted on grade X students of a public senior high school in Karangbinangun, Lamongan, Indonesia, on opportunity material by applying Problem-Based Learning (PBL) model. This study aims to determine the effect of the PBL model on students' numeracy ability in solving Asesmen Kompetensi Minimum (AKM) problems on opportunity material. This research is quantitative research using a nonequivalent control group design. The sampling technique used in this study was purposive sampling. Data collection techniques in this study used test instruments, whereas the validity, reliability, differentiating power, and difficulty index have been explained. The data analysis techniques used independent sample t-test and N-gain test. The results showed that applying the PBL model could improve the numeracy ability of students in solving AKM problems on opportunity material. This is evidenced by the difference in the average post-test score obtained by students in the experimental class (88) and in the control class (84). Based on the calculation of the average pretest and post-test in both classes, the percentage of numeracy ability of students in the experimental class was 55.62%, while the percentage of numeracy ability of students in the control class was 51.73%. The calculation of the independent sample t-test also shows significance in the value of sig. (2-tailed) less than 0.05 (0.000 < 0.05). Therefore, the PBL model affects students' numeracy abilities.